Exploring salt sensitivity in berseem (Trifolium alexandrinum) through analysis of ROS-scavenging attributes - JOHAL, N; SONKAR, I; KAUR, H; KAUR, S (The Indian Journal of Agricultural Sciences, 2025)
Berseem (Trifolium alexandrinum L.) serves as an excellent fodder source, yet its limited salt tolerance restricts its cultivation. This study was carried out during 2022 and 2023 at Indian Institute of Technology, Ropar, Punjab to examine the impact of salinity stress (2.5, 5.0, and 6.5 dS/m) imposed at different growth stages (2-leaf, 6-leaf, and flowering) on berseem in a sensor-based lysimeter system. The control group was irrigated with tap water in and completely randomised block (CRD) design was followed. Growth attributes and antioxidative potential were assessed. The results revealed that salt stress significantly reduced plant height (by up to 33%), biomass (by up to 68%), and root length (by up to 59%), with the most severe decline observed at 6.5 dS/m at the 6-leaf stage. Pearson’s correlation matrix indicated a strong positive correlation between H₂O₂ content and MDA (r = 0.78) and a moderate positive correlation with SOD (r = 0.58). The activities of antioxidative enzymes, peroxidase and superoxide dismutase, exhibited a significant up-regulation by 525% and 71%, respectively as salinity increased from control to 6.5 dS/m. Principal component analysis confirmed that the 6-leaf stage was the most salt-sensitive. The critical damage threshold for berseem was identified at salinity levels exceeding 5 dS/m.